What about the men, though? Relative wage opportunities and the persistence of employment gaps in couples - Luisa Hammer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2025)
Gender gaps in employment have narrowed but remain substantial, particularly among couples. To estimate how improved female wage opportunities influence partners' employment choices, I exploit demand-driven wage changes in job tasks and German administrative data. Results indicate women respond positively, albeit at a diminishing rate, to relative wage improvements, while male partners also increase their labor supply in response. Consequently, the work hours gap within couples narrows, but doesn't close and even widens in certain groups. Potential explanations for these patterns building on Becker's household model include comparative advantages for women, and relative income preferences and gender identity norms for men. – – Die geschlechtsspezifischen Unterschiede bei der Beschäftigung haben sich verringert, sind aber nach wie vor beträchtlich, insbesondere innerhalb von Paaren. Um abzuschätzen, wie sich verbesserte Lohnmöglichkeiten für Frauen auf die Beschäftigungs- entscheidungen der Partner auswirken, nutze ich nachfragegesteuerte Lohnveränderungen bei Arbeitsaufgaben und deutsche Verwaltungsdaten. Die Ergebnisse deuten darauf hin, dass Frauen positiv, wenn auch mit abnehmender Tendenz, auf relative Lohnverbesserungen reagieren, während männliche Partner als Reaktion darauf ebenfalls ihr Arbeitsangebot erhöhen. Infolgedessen verringert sich die Arbeitszeitlücke innerhalb von Paaren, schließt sich aber nicht und vergrößert sich in bestimmten Gruppen sogar. Mögliche Erklärungen für diese Muster, die auf Beckers Haushaltsmodell aufbauen, sind komparative Vorteile für Frauen sowie relative Einkommenspräferenzen und Geschlechtsidentitätsnormen für Männer.
Keywords: D13; E32; J12; J16; J22; 330; Gender pay gap; female employment; household specialization; structural change